L’Artemision rupestre di Scala Greca a Siracusa: alcune note sui frammenti coroplastici conservati - Beatrice Risposi (Les Carnets de l’ACoSt)
The paper presents the most significant of the terracotta fragments from the rocky sanctuary of Scala Greca, at the northern end of the Syracusan plateau, now exhibited at the ‘Paolo Orsi’ Regional Archeological Museum. Their study has made it possible to develop a typology of the best represented iconographic type, that of “Artemide Sicula”. It is likely that Artemis was venerated there with the epiclesis of Agrotera, though chthonic connotations of the cult are not to be excluded.